Naoxintong Capsule Inhibits the Development of Cardiovascular Pathological Changes in Bama Minipig Through Improving Gut Microbiota - Zhang, Wei-jian; Su, Wei-wei; Li, Pei-bo; Rao, Hong-yu; Lin, Qing-wei; Zeng, Xuan; Chen, Tao-bin; Yan, Zeng-hao; Liu, Hong; Yao, Hong-liang (Frontiers in Pharmacology, 2019)
There are a great variety of risk factors develop and change over time from dyslipidemia to cardiovascular diseases. During the complex pathological process, traditional Chinese medicine exert excellent multi-path performances as evidenced by numerous works. Naoxintong capsule (NXT), a Chinese medicine, has performed excellent effects on the prevention and treatment against cardiovascular diseases. NXT is a fine powder mixture without any herb extraction, and there must be lots of ingredients hard to be absorbed and enter the bloodstream. Accordingly, this study was designed on the hypothesis that NXT’s effects against the cardiovascular diseases are partly through ameliorating blood lipid metabolism disorders and partly through improving gut microbiota. In this study, minipigs, due to the closely similarity to human being in the lipoprotein metabolism profiles and cardiovascular systems, were selected and fed with high-fat diet and NXT daily for successive 8 months. During the process, up to 18 biomedical parameters were detected once per month to observe the dynamic changes after NXT treatment. At the end of experimental process, pathological examinations of heart, liver, coronary artery, carotid artery, thoracic aorta and abdominal aorta were conducted by HE staining and Oil red staining, and 16SrDNA sequencing and analyzing of gut microbiota were conducted. The results showed that NXT’s effects against blood lipid metabolism disorders were through regulating blood lipid profiles, inhibiting vascular inflammation, enhancing antioxidant capacity, and alleviating myocardial injury, without damages on liver and kidney particularly. On the other hand, long-term NXT administration increased the diversity of gut microbiota stably, and revered the increase of the ratio of the Firmicutes to Bacteroidetes (F/B ratio) in relative abundance. Specifically, the key bacteria were the Caproiciproducens (enhanced), Sutterella (enhanced), Erysipelotrichacea (enhanced) and Romboutsia (decreased).